2012
DOI: 10.1111/hex.12006
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ engagement in primary care: powerlessness and compounding jeopardy. A qualitative study

Abstract: Background Primary health care does not adequately respond to populations known to have high needs such as those with compounding jeopardy from chronic conditions, poverty, minority status and age; as such populations report powerlessness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
127
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(134 citation statements)
references
References 33 publications
5
127
1
1
Order By: Relevance
“…2,3 Data from surveys and qualitative and observational research indicate that clinicians often do not take patients' perspectives into account; rather, clinicians often promote or recommend specific treatments rather than consider patients' preferences during the decision-making process. [4][5][6][7] Clinicians are commonly challenged by the diversity of situations that arise in practice when they attempt to implement patient-centered care. For example, providing patient-centered care for a patient at the end of life is very different from counseling a patient with a long-term health condition or providing advice about preventative care.…”
mentioning
confidence: 99%
“…2,3 Data from surveys and qualitative and observational research indicate that clinicians often do not take patients' perspectives into account; rather, clinicians often promote or recommend specific treatments rather than consider patients' preferences during the decision-making process. [4][5][6][7] Clinicians are commonly challenged by the diversity of situations that arise in practice when they attempt to implement patient-centered care. For example, providing patient-centered care for a patient at the end of life is very different from counseling a patient with a long-term health condition or providing advice about preventative care.…”
mentioning
confidence: 99%
“…These findings affirm other work identifying a relative absence of a patient-centered perspective. 6,20 In some consultations, the focus was on simply providing information, 40 with relatively little emphasis on the structured negotiation techniques noted previously to effect lifestyle change. 29 Furthermore, the requirement to use a structured checklist approach can lead to loss of more engaged communication technique, as was seen in the interaction of NS13 and PT03.…”
Section: Communication and Patient-centerednessmentioning
confidence: 99%
“…3 Although the impact of diabetes is largely a function of both social determinants of health and genetic predisposition, 3,4 an important determinant of outcome in primary care settings is the effectiveness of the consultation between patients and health care professionals. 5,6 Diabetes management is now focused on primary care settings 7 and multidisciplinary team care. 8 Multidisciplinary care presents challenges related to the consultation styles 9 of different health professionals, 10 and the different relationships patients develop by engaging in a linked sequence of consultations with professionals from both primary and secondary care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that clinicians must Adapted from [46,52] be willing to be guided by their patients' perceptions of need, not by their own assumptions of similarity and beliefs about illness and clinical management. As chronic conditions such as CVD are increasingly managed within the primary healthcare sector, Government policy must advocate greater engagement with vulnerable populations that emphasize health equity and provide incentives to general practitioners to adopt new approaches [58].…”
Section: Cultures Apartmentioning
confidence: 99%